Matrifocal (Dis)ease and (Re)membering in Amy Kurzweil’s Flying Couch - Ragsdale- Richards, Marybeth (FRAME, Journal of Literary Studies, 2026)
“Matrifocal (Dis)ease and (Re) membering in Amy Kurzweil’s Flying Couch” provides an interdisciplinary reading of Kurzweil’s graphic memoir that combines space and place theory with comics scholarship, trauma studies, and family systems theory. Through tightly pairing the act of remembering with illustrations of putting bodies back together again on the page, Kurzweil grapples with matrilineal trauma connected to her grandmother, a Shoah survivor, and the traumatic recall of her own third-generation inheritance. This article argues that Flying Couch is Kurzweil’s postmemorial project and is uniquely poised to engage readers in the act of bearing witness as a creative, continuous process.